Design and modelling of dual active bridge DC-DC converter for integration of energy storage system - Yeo, Kevin Eng Lye (2018)
This paper will be analysing two different converters, mainly a AC-AC converter with zero voltage switching (ZVS) and a DC-DC dual active bridge (DAB) converter. Firstly, it will require gaining understanding of how an AC-AC converter works, together with the fundamentals such as the components and eventually the pulse wave modulator (PWM) to control the signal being sent to the control switches. After calculating the parameters of the AC-AC converter, it will be simulated using PSIM software. The same will be done with the DC-DC DAB converter where parameters will be derived, and the output waveforms will be observed and analysed through the use of PSIM simulation. By analysing the waveforms, the topology will then be available for further testing with components for a model for real-life testing.